Analyzing Student Teachers of English Listening Fluency Level: A Preliminary Research - Refi Ranto Rozak; Mursid Shaleh; Dwi Anggani Linggar Bharati; Djoko Sutopo (IKIP PGRI Bojonegoro, 2019)
AbstractAlthough listening comprehension remains a widely acknowledged tool for assessing and evaluating student teachers’ achievement in mostly Indonesian initial teacher education (ITE) context, the issue of listening fluency (LF) as one of the four strands of well-balanced language course has not received scholarly attention. However, in fact, LF is important for developing their automatic aural processing on authentic exposures. In response to this gap, this article discussed the result of LF test via graded serial news stories in normal speech rates to 60 English student teachers of a private ITE institution in the northern part of East Java Province, Indonesia, to examine their LF levels. Additionally, various responses of LF experience, massive spoken texts experience, spoken features inhibition, and LF instruction evaluative feedbacks were garnered as additional qualitative data via interview responses at the end of the research as well. The data obtained were then tabulated, categorized, and analyzed. The finding of the research mainly found that, on average, their LF score was 66. It reveals that their LF level was under the normal speech rate required in longer aural texts found in real-life listening. The findings may raise the awareness of possibility including LF in the prescribed listening curriculum for training student teachers’ language proficiency. AbstrakWalaupun pemahaman menyimak secara luas dikenal sebagai alat penilaian dan evaluasi prestasi mahasiswa calon guru di hampir semua institusi pendidikan calon guru di Indonesia, isu kelancaran menyimak sebagai salah satu dari empat pilar program bahasa yang berimbang belum secara ilmiah mendapat perhatian. Meskipun demikian, kelancaran menyimak dirasa penting untuk mengembangkan proses pemahaman teks lesan otentik secara otomatis. Oleh karena itu, artikel ini memaparkan hasil tes menyimak via teks lesan berita serial berjenjang dalam tingkat kecepatan normal terhadap 60 mahasiswa calon guru bahasa Inggris di sebuah institusi keguruan di bagian utara Provinsi Jawa Timur untuk menguji tingkat kelancaran menyimak mereka. Selain itu, beragam respons pengalaman mahasiswa tentangkelancaran menyimak, pengalaman menyimak teks lesan masif, hambatan-hambatan dalam bahasa lesan, dan umpan balik evaluatif terkait pengajaran kelancaran menyimak dikumpulkan sebagai data kualitatif melalui wawancara di akhir penelitian. Data yang telah diperoleh kemudian ditabulasi, dikategorisasi, dan dianalisa. Temuan utama penelitian ini adalah kelancaran menyimak mahsiswa calon guru bahasa Inggris rata-rata masih rendah, yaitu sebesar 66. Hal ini berarti tingkat kelancaran menyimak mereka masih di bawah tingkat kecepatan normal yang dipersyaratkan dalam memahami teks lesan panjang dalam situasi menyimak sehari-hari. Temuan ini menumbuhkan kesadaran akan kemungkinan memasukkan kelancaran menyimak dalam kurikulum menyimak untuk melatih kemahiran berbahasa mahasiswa calon guru bahasa Inggris.